Hyperglycemia in pediatric head trauma patients: a cross-sectional study Hiperglicemia em pacientes pediátricos com traumatismo craniencefálico: estudo de corte transversal - José Roberto Tude Melo; Rodolfo Casimiro Reis; Laudenor Pereira Lemos-Júnior; Henrique Miguel Santos Coelho; Carlos Eduardo Romeu de Almeida; Jamary Oliveira-Filho (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To verify the prevalence of acute hyperglycemia in children with head trauma stratified by the Glasgow coma scale (GCS). METHOD: A prospective cross-sectional study carried out with information from medical records of pediatric patients presenting with head injury in the emergency room of a referral emergency hospital during a one year period. We considered the cut-off value of 150 mg/dL to define hyperglycemia. RESULTS: A total of 340 children were included and 60 (17.6%) had admission hyperglycemia. Hyperglycemia was present in 9% of mild head trauma cases; 30.4% of those with moderate head trauma and 49% of severe head trauma. We observed that among children with higher blood glucose levels, 85% had abnormal findings on cranial computed tomography scans. CONCLUSION: Hyperglycemia was more prevalent in patients with severe head trauma (GCS <8), regardless if they had or not multiple traumas and in children with abnormal findings on head computed tomography scans. OBJETIVO: Verificar a prevalência de hiperglicemia aguda em crianças vítimas de trauma craniencefálico, de acordo com a escala de coma de Glasgow (GCS). MÉTODO: Estudo prospectivo, de corte transversal realizado por meio do acompanhamento de prontuários médicos de pacientes na faixa etária pediátrica admitidos na unidade de urgência de um hospital de referência vítimas de traumatismo craniencefálico, durante um ano. Consideramos o valor de corte em 150 mg/dL para definição de hiperglicemia. RESULTADOS: 340 crianças foram incluídas no estudo e 60 (17,6%) apresentaram hiperglicemia na admissão. Hiperglicemia esteve presente em 9% dos casos de trauma craniano leve, 30,4% daqueles com trauma craniano moderado e em 49% dos pacientes com trauma craniano grave. Verificamos que, entre as crianças com níveis elevados de glicemia, 85% apresentavam alterações radiológicas verificadas na tomografia computadorizada do crânio. CONCLUSÃO: A hiperglicemia foi mais prevalente em pacientes com traumatismo craniano grave (GCS <8), assim como naqueles com alterações identificadas na tomografia computadorizada do crânio, independente da presença de politraumatismo.